Ability of cecropin B to penetrate the enterobacterial outer membrane. - Vaara, M (1994)
The cationic amphipathic insect peptide cecropin B was almost as active on wild-type enteric bacteria as it was on their lipopolysaccharide and lipid A mutants that have very defective outer membrane. The polymyxin-resistant strains, which elaborate altered, less anionic lipopolysaccharide, were completely susceptible to cecropin B. No synergism was found between cecropin B and hydrophobic antibiotics. Throughout the study, the activity of cecropin B resembled that of quaternary detergents.